2004
DOI: 10.4054/mpidr-wp-2004-018
|View full text |Cite
|
Sign up to set email alerts
|

The demographics of same-sex „marriages“ in Norway and Sweden

Abstract: Working papers of the Max Planck Institute for Demographic Research receive only limited review. Views or opinions expressed in working papers are attributable to the authors and do not necessarily reflect those of the Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 14 publications
8
60
0
1
Order By: Relevance
“…Controlling for marriage and coresidence, lesbian couples have significantly less stability than heterosexual couples or gay male couples (see Table 2). Other studies of same-sex couple longevity have reported a greater break-up rate of lesbian couples as compared to gay male couples (Andersson et al, 2006;Blumstein & Schwartz, 1983;Ross et al, 2011), but the reasons for the gender gap in same-sex couple longevity are not clear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Controlling for marriage and coresidence, lesbian couples have significantly less stability than heterosexual couples or gay male couples (see Table 2). Other studies of same-sex couple longevity have reported a greater break-up rate of lesbian couples as compared to gay male couples (Andersson et al, 2006;Blumstein & Schwartz, 1983;Ross et al, 2011), but the reasons for the gender gap in same-sex couple longevity are not clear.…”
Section: Discussionmentioning
confidence: 98%
“…At least four studies have used populationbased samples to analyze same-sex couple longevity in Europe. Andersson, Noack, Seierstad, and Weedon-Fekjaer (2006) found that gay male couples with registered partnerships in the 1990s in Sweden had a risk of breakup similar to heterosexual married couples, whereas lesbian couples with registered partnerships had rates of breakup two to three times higher than the break-up rate of heterosexual married couples. Kalmijn, Loeve, and Manting (2007) found that same-sex cohabiting couples had odds of breakup three times higher than heterosexual cohabiting couples and 11 times higher than heterosexual married couples.…”
Section: Previous Research On Same-sex Couple Relationship Longevitymentioning
confidence: 96%
“…In a study of the demographics of same-sex marriage in Norway and Sweden, it was stated that patterns in divorce risks are rather similar in same-sex and opposite-sex marriages, but divorce risk levels are considerably higher in same-sex marriages. 43 Further studies are essential to understand relationship breakup in lesbian couples.…”
Section: Discussionmentioning
confidence: 99%
“…According to official ISTAT (Italian National Institute of Statistics) residence data, on 1 January 2018, 13,256 Italians were living in same-sex partnerships. 3 The numbers are very small (4.64 people in same-sex partnership per 10,000 married people), but seem to be in line with the numbers observed in Northern Europe immediately after the passage of similar bills 4 (Andersson, Noack, Seierstad, & Weedon-Fekjaer, 2006). As is to be expected, same-sex couples have predominantly settled in Northern Italy and in larger urban areas.…”
mentioning
confidence: 59%